Peer Effects and Social Networks in Education - Antoni Calvo-Armengol; Eleonora Patacchini; Yves Zenou (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
This paper studies whether structural properties of friendship networks affect individual outcomes in education. We first develop a model that shows that, at the Nash equilibrium, the outcome of each individual embedded in a network is proportional to her Katz-Bonacich centrality measure. This measure takes into account both direct and indirect friends of each individual but puts less weight to her distant friends. We then bring the model to the data by using a very detailed dataset of adolescent friendship networks. We show that, after controlling for observable individual characteristics and unobservable network specific factors, the individual's position in a network (as measured by her Katz-Bonacich centrality) is a key determinant of her level of activity. A standard deviation increase in the Katz-Bonacich centrality increases the pupil school performance by more than 7 percent of one standard deviation.
Keywords: A14; C31; C72; I21; 330; Centrality measure; peer influence; network structure; school performance